Molecular Cloning, Nucleotide Sequence, and Expression of Genes Encoding a Polycyclic Aromatic Ring Dioxygenase from Mycobacterium sp. Strain PYR-1 - Khan, Ashraf A. (American Society for Microbiology, 2001)
Mycobacterium sp. strain PYR-1 degrades high-molecular-weight polycyclic hydrocarbons (PAHs) primarily through the introduction of both atoms of molecular oxygen by a dioxygenase. To clone the dioxygenase genes involved in PAH degradation, two-dimensional (2D) gel electrophoresis of PAH-induced proteins from cultures of Mycobacterium sp. strain PYR-1 was used to detect proteins that increased after phenanthrene, dibenzothiophene, and pyrene exposure. Comparison of proteins from induced and uninduced cultures on 2D gels indicated that at least six major proteins were expressed (105, 81, 52, 50, 43, and 13 kDa). The N-terminal sequence of the 50-kDa protein was similar to those of other dioxygenases. A digoxigenin-labeled oligonucleotide probe designed from this protein sequence was used to screen dioxygenase-positive clones from a genomic library of Mycobacterium sp. strain PYR-1. Three clones, each containing a 5,288-bp DNA insert with three genes of the dioxygenase system, were obtained. The genes in the DNA insert, from the 5′ to the 3′ direction, were a dehydrogenase, the dioxygenase small (β)-subunit, and the dioxygenase large (α)-subunit genes, arranged in a sequence different from those of genes encoding other bacterial dioxygenase systems. Phylogenetic analysis showed that the large α subunit did not cluster with most of the known α-subunit sequences but rather with three newly described α subunits of dioxygenases from Rhodococcus spp. and Nocardioides spp. The genes from Mycobacterium sp. strain PYR-1 were subcloned and overexpressed in Escherichia coli with the pBAD/ThioFusion system. The functionality of the genes for PAH degradation was confirmed in a phagemid clone containing all three genes, as well as in plasmid subclones containing the two genes encoding the dioxygenase subunits.